SK Channel Modulates Synaptic Plasticity by Tuning CaMKIIα/β Dynamics - Shrestha, Amita; Sultana, Razia; Lee, Charles C.; Ogundele, Olalekan M. (Frontiers in Synaptic Neuroscience, 2019)
NMDAR-linked Ca++ current represents a significant percentage of post-synaptic transient Ca++ current. It is pertinent to the modulation of synaptic strength that underlie dendritic spine plasticity and cognitive function. In the hippocampus, synaptic potentiation is tuned by CaMKIIα Thr286/287 phosphorylation. On the other hand, post-synaptic transient Ca++ current produced by glutamatergic ionotropic neurotransmission repetitively activates small conductance (SK2) channels which in turn abrogates the potentiation event. Here, we demonstrate that the upstream suppression of GluN1 function in the CA1 of the hippocampus suppressed T286/T287 phosphorylation of CaMKII, and was accompanied by an increased SK2 expression, and activity. Consistent with the ablation of GluN1 function, positive modulation of SK2 in wild type hippocampus (normal GluN1) decreased T286/T287 phosphorylation of CaMKII, and bursting frequency that is determined - mostly - by T286 CaMKII. Together with the suppression of T287 phosphorylation of CaMKIIβ, a significant loss of hippocampal -actinin suggests that SK2 impact spine localization of CaMKII, and its substrate targeting downstream of NMDAR. Our results demonstrate that positive modulation of SK2 function in the CA1 refines synaptic plasticity by attenuating CaMKII T286/T287 phosphorylation, and synaptic localization.